Evaluating the International Renewable Energy Agency Through the Lens of Social Constructivism - Mengi-Dincer, H.; Ediger, V. S.; YESEVİ, ÇAĞLA GÜL (Pergamon-Elsevier Science Ltd., 2021)
It is widely accepted that renewable energy will contribute to building a more sustainable world, and a transition from a fossil fuel-dominated to a renewable-based energy system is inevitable. However, only 5% of the world's primary energy consumption comes from renewables. It will, therefore, take considerable time to implement international policies and take effective actions to increase the use of renewable energy to a level that mitigates climate change. States remain the primary decision-makers in the international structure, but international organizations can help states internalize and form new identities by creating norms. It is expected that the International Renewable Energy Agency (IRENA) will have a voice on international renewable energy policies. This study seeks to explain how IRENA helps shape these policies through its interactions with major players. It examines the agency's activities, initiatives, and tools over the past 10 years, and how it contributes to norm emergence and identity creation in renewable energy through social constructivism. Using the constructivist approach, this study argues that IRENA's efforts to create norms have succeeded to a considerable extent, but the agency needs to spread its initiatives more equally around the world so that these norms become truly universal. Today, nearly every state needs to improve its renewable energy policies. This objective may only be possible if states form a common identity through the internalization of renewable energy norms. IRENA still has a lot of work to do.
Keywords: IRENA; Global Renewable Energy Governance; Energy Transition; Social Constructivism